2016
DOI: 10.1055/s-0036-1580708
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Functionality of Pelvic Floor Muscles and Sexual Satisfaction in Young Women

Abstract: Objective The objective of this study is to associate the results obtained while assessing the pelvic floor muscles (PFM) functionality with the score of sexual satisfaction of young adult women. Methods This is an observational and cross-sectional study. The inclusion criteria were women aged between 20 and 40 years who have had sexual intercourse, nulliparous, BMI lower than 25 kg/m 2 , and absence of pelvic floor dysfunction. The evaluation consisted of both the medical history and assessment of the PFM fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
3
1
1
Order By: Relevance
“…19 No evidence has demonstrated any possible association between PFM function and sexual satisfaction. 20 In contrast, our study revealed that the presence or absence of FSD correlated with the peak EMG amplitude during the phasic (flick) contractions and the recovery latency during the tonic contractions among all the PFM EMG parameters, possibly due to differences in the study population.…”
Section: Discussioncontrasting
confidence: 89%
“…19 No evidence has demonstrated any possible association between PFM function and sexual satisfaction. 20 In contrast, our study revealed that the presence or absence of FSD correlated with the peak EMG amplitude during the phasic (flick) contractions and the recovery latency during the tonic contractions among all the PFM EMG parameters, possibly due to differences in the study population.…”
Section: Discussioncontrasting
confidence: 89%
“…Female sexual satisfaction is a complex phenomenon, which may be assessed with a variety of predictors, including social and psychological factors. It can be treated as an important indicator in the field of sexual health and a crucial determinant of well-being and the quality of life [8,18,19]. The study showed that satisfaction with life of the Polish women surveyed reached the average level reported in other economically developed countries.…”
Section: Discussionmentioning
confidence: 83%
“…Human sexuality is very complex and influenced by a multitude of factors, including biological, psychological, social and cultural [5,7,8]. Ensuring sexual health is based on fulfilling one's individual sexual needs and being able to to make informed choices about one's sexual life [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tai dažna sveikatos problema, kuri neigiamai veikia asmens fizinę, psichologinę ir socialinę būklę, prastina gyvenimo kokybę, skatina depresijos atsiradimą [3]. Dažnai vienu iš suprastėjusios gyvenimo kokybės komponentų tampa seksualinė disfunkcija (SD), kurios pagrindinės priežastys yra ŠN baimė lytinių santykių metu, drovėjimasis dėl kvapo [4][5]. Nors SD paplitusi tarp abiejų lyčių, tačiau moterims šis sutrikimas pasireiškia dažniau -nuo 25 proc.…”
Section: Santraukaunclassified